Physio-agronomic characteristics and andrographolide yield of Andrographis paniculata in response to endophytic Bacillus sp and phosphorus - Gusmaini, Gusmaini; Nurhayati, Hera; Kartika, Kartika; Putra, Sunjaya; Sasmita, Kurnia Dewi; Rismayani, Rismayani; Saefudin, Saefudin; Wibawa, Wahyu; Pranowo, Dibyo; Wardiana, Edi; Ferry, Yulius; Yunita, Rossa; et al. (Frontiers in Agronomy, 2025)
Endophytic bacteria can be applied as biofertilizers and plant growth promoters due to their potential to release phytohormones and improve nutrient availability, thereby supporting plant growth and the biosynthesis of bioactive compounds. Effective practical cultivation of medicinal plants, including sambiloto (Andrographis paniculata), suggests using biofertilizer, in addition to inorganic fertilizer. Andrographolide, a key compound in A. paniculata, is recognized for its therapeutic properties, including anti-inflammatory and antiviral activities, making its enhanced biosynthesis significant in medicinal plant research. Phosphorus is required in andrographolide biosynthesis. The study aimed to determine the physiological and agronomic characteristics, as well as the bioactive compounds of A. paniculata, by applying endophytic bacteria and phosphate fertilizer. The trial was arranged in a completely randomized design with six treatments and three replications. The treatments consisted of the following: 1) no treatment (control), 2) 0.675 g P2O5 plant-1, 3) 1.35 g P2O5 plant-1, 4) endophytic bacteria Bacillus sp., 5) endophytic bacteria Bacillus sp. + 0.675 g P2O5 plant-1, and 6) endophytic bacteria Bacillus sp. + 1.35 g P2O5 plant-1. Endophytic bacteria Bacillus sp. and phosphate fertilizer significantly (P<0.05) influenced agronomic characteristics, including growth and fresh and dry biomass production, as well as physiological characteristics, including Net Assimilation Rate (NAR), Relative Growth Rate (RGR), Stem-to-Leaf Ratio (SLR), Leaf Area Index (LAI), and Leaf Area Ratio (LAR). The application of Bacillus sp. in combination with 0.675 g P2O5 plant-1 produced the highest herbage weight and secondary metabolites (andrographolide, 14-deoxy-11,12-didehydroandrographolide, and neo-andrographolide), and hence could be recommended in A. paniculata cultivation. Furthermore, the application of endophytic bacteria Bacillus sp. could reduce the use of chemical phosphate fertilizer by 50%, offering significant benefits for farmers and being more environmentally friendly to support sustainable agriculture.